COMMUNITY EMPOWERMENT THROUGH UTILIZATION OF LIVESTOCK WASTE AS ORGANIC FERTILIZERAND ITS APPLICATION IN HORTICULTURAL PLANTS IN BOBAWA VILLAGE, MALIFUT DISTRICT, NORTH HALMAHERA REGENCY - Yunus Syafie; Nurdiyanawati Djumadil (Bajang Institute, 2022)
Empowerment is a form of efforts made by groups or communities who initiate the process of social activities in order to improve their own situation and condition, or in other words, the empowerment can also help farmers who have been experiencing difficulties, it also help the farmers by improve their welfare. In this regard, the Community Partnership Program (CPP) can be one of the community service programs that integrates academic activities with the dharma of service, so that it cancreate both soft skills and hard skills needed by communities. The aim of this service activity was to improvefarmers’ awareness in farmer groups to join as partners, so that they want, know, and adopt science, skills, and technology in producing organic fertilizer from livestock waste (animal waste) that is environmentally friendly. This CPP activity has been conducted through socialization and training, as well as practical work starting from the preparation of materials to the process into organic fertilizer products of livestock waste that canbe used on horticultural crops (vegetables); this can reduce the use of chemical fertilizers,resulting in a higher quality of the harvested vegetables.